Water and Earthquakes - Wang, Chi-Yuen (Lecture Notes in Earth System Sciences, 2021)
This open access book explores the interactions between water and earthquakes, including recent concerns about induced seismicity. It further highlights that a better understanding of the response of the water system to disturbances such as earthquakes is needed to safeguard water resources, to shield underground waste repositories, and to mitigate groundwater contamination. Although the effects of earthquakes on streams and groundwater have been reported for thousands of years, this field has only blossomed into an active area of research in the last twenty years after quantitative and continuous documentation of field data became available. This volume gathers the important advances that have been made in the field over the past decade, which to date have been scattered in the form of research articles in various scientific journals.